Dynamic functional assessment of T cells reveals an early suppression correlating with adverse outcome in polytraumatized patients - Jooss, Tobias; Maier, Katharina; Reichardt, Lena-Marie; Hindelang, Bianca; Süberkrüb, Lönna; Hamberger, Kim Lena; Bülow, Jasmin Maria; Schuetze, Konrad; Gebhard, Florian; Mannes, Marco; Halbgebauer, Rebecca; Wohlgemuth, Lisa; et al. (Frontiers in Immunology, 2025)
IntroductionMost trauma patients require intensive care treatment and are susceptible to developing persistent inflammation and immunosuppression, potentially leading to multi organ dysfunction syndrome (MODS) and dependence on long term care facilities. T cells undergo changes in numbers and function post trauma. T cell dysfunction in polytraumatized patients was characterized using functional immunomonitoring to predict individual clinical outcome. Moreover, the potential to reverse T cell dysfunction using Interleukin (IL)-7 was examined.MethodsBlood samples were drawn from healthy individuals and prospectively enrolled polytrauma patients (Injury Severity Score ≥ 18) on admission, 8, 24 and 48 hours, 5 and 10 days after. CD3/28-stimulated cytokine production of T cells in whole blood was assessed via Enzyme Linked Immuno Spot (ELISpot). T cell subsets were quantified via counting and flow cytometry. Unfavorable physical performative outcome was defined as death or new functional disability necessitating long term care. Secondary outcomes were the development of MODS and in-hospital mortality. IL-7 was added ex vivo to test reversibility of cytokine disturbances.Results34 patients were enrolled. The different outcome groups showed no difference in injury severity. Patients with favorable physical performative outcome revealed higher functional T cell specific Interferon γ (IFN-γ) and IL-17 (8 hours) and lower IL-10 production (day 5) and higher CD8 T cell concentrations. Patients without MODS development showed a higher IFN-γ (day 10), higher IL-2 (8 hours) and higher IL-17 production (admission, day 5). There were no differences regarding in-hospital mortality. Systemic blood IFN-γ, IL-2 and IL-10 concentrations only correlated with MODS (24 hours). Systemic CD8 T cell numbers correlated with functional IFN-γ production. Whole blood stimulation with IL-7 increased functional T cell IFN-γ release.DiscussionOur study reveals an early characteristic overall T cell dysfunction of pro-inflammatory (IFN-γ, IL-2, IL-17) and immunosuppressive (IL-10) subtypes in polytraumatized patients. Our data indicates that rather the functional capacity of T cells to release cytokines, but not systemic cytokine concentrations can be used to predict outcome post trauma. We assume that the early stimulation of pro- and anti-inflammatory T cells benefits polytraumatized patients. Potentiation of functional IFN-γ release might be achieved by IL-7 administration.